Nghozi na Nxungeto Ku valanga nhlamuselo hi tihlo ra tindzimi ta Afrika (Dzonga): Mhaka ya Xitsonga eka mbulavulo wa khombo - Norman Mathebula; Morris T. Babane; Jabulani C. Makhubele; Kingsley K. Ayisi; Wiseman N. Mathebula; Prudence Mafa; Josephine M. Letsoalo; Mzamani S. Khosa; Meshack O. Shilenge (Jàmbá)
Disaster and Risk! Exploring meaning through the lens of (South) African languages: A case of Xitsonga language in disaster communication. Even though there is a difference between the disaster management-related terms disaster itself, crisis, and emergency, they are closely interconnected, interdependent, and overlap significantly. With a blurred line between the definitions of these terms, the mainstream literature uses the terms disaster, crisis, and emergency interchangeably and in combination such as ‘disaster crisis management’ and ‘crisis and emergency management’. The aim of this article is to explore the various meanings of ‘disaster’ within the cultural, communication, and language context of the Xitsonga speakers. A qualitative conceptual content analysis has been carried out to establish the differences and similarities between the disaster terms based on interviews with the Xitsonga speaker. The analysis reveals that all are associated with the sudden nature of the event and the damage caused in the process. Furthermore, the study found that there are many common features associated with the terms leading to them being used interchangeably up to a certain extent. There were differences regarding some terms such as ‘danger’ based on the selected two regions of the Xitsonga population.